Botani, ekologi, fitokimia, bioaktivitas, dan pemanfaatan pucuk merah (Syzygium myrtifolium Walp.) di Indonesia: Suatu Kajian Pustaka - Setiawan, Dimas Ario; Wakhidah, Anisatu Z. (Jurnal Biologi Udayana, 2023)
Kelat oil ( Syzygium myrtifolium Walp.) is one of the most popular ornamental plants in Indonesia. However, apart from having potential in the economic aspect, this plant also has the potential to be used holistically to support the manufacture of herbal medicines. The purpose of this research is to increase the scope of studies on the use of kelat oil by the community. This research was conducted using the study method and literature analysis which included ecology, botany, phytochemistry, bioactivity and utilization of kelat oil. The research method is to examine published scientific articles online search results through google scholar and researchgate with keyword that connected to Syzygium myrtifolium such as botanical and ecological, utilization, local use, ethnobotany, phytochemical content, and bioactivity of Syzygium myrtifolium . The results of this study explain that the leaves of the kelat oil plant have several phytochemicals such as flavonoids and alkaloids which has bioactivity and potentially as an ingredient for making medicines, antiseptics, antibacterial, antidiabetics, antihypertension, and rehabilitative efforts for burns. In general, the use of red shoots by people in Indonesia is as an ornamental plant, supporting reforestation activities, mitigating floods and landslides, as a support for outdoor learning, and also as a complement to religious ceremonies.